THE USE OF ENGLISH IN IMUN (INTERNATIONAL MODEL UNITED NATIONS) - Hana Theresya Nisa; Didit Kurniadi; Amin Khudlori (Jurnal CULTURE (Culture, Language, and Literature Review), 2022)
English is an international language that needs to be mastered by people who want to connect with other people from all over the world. Studying at a school or course institution is not enough to facilitate someone in speaking English quickly. There must be direct communication that is done to improve speaking skills. One of the international organizations that gives a person free space to use English is IMUN (International Model United Nations). IMUN is a simulation forum for the UN session that aims to mobilize young people from all over the world to express their opinions on international issues, which ultimately seeks to find a solution to a series of existing problems. This study's objective is to investigate English use in IMUN. The researchers use the descriptive qualitative method with the participation method as the primary data, and the screen captures of video or photo method to obtain additional data. One of the author's direct involvements in the Internship at IMUN (Campus Ambassador) and the simulation of the UN session (Online Conference) reinforce the fact that IMUN is truly an international organization that can be used as a forum to improve English language skills. With those experiences, the participants can improve their English skills quickly.